"순환군"의 두 판 사이의 차이

40 바이트 추가됨 ,  1년 전
편집 요약 없음
** 증명: 우선, <math>G/\langle b\rangle=\langle a\langle b\rangle\rangle\times(B/\langle b\rangle)=(\langle a\rangle/\langle b\rangle)\times(B/\langle b\rangle)=(\langle a\rangle B)/\langle b\rangle</math>이므로, <math>G=\langle a\rangle B</math>이다. 또한, <math>(\langle a\rangle\cap B)/\langle b\rangle\subseteq(\langle a\rangle/\langle b\rangle)\cap(B/\langle b\rangle)=\{\langle b\rangle\}</math>이므로, <math>\langle a\rangle\cap B\subseteq\langle a\rangle\cap\langle b\rangle=1</math>이며, <math>G=\langle a\rangle\times B</math>이다.
{{증명 끝}}
 
==함께보기==
*[[실로우 정리]]
 
== 외부 링크 ==